Karakteristik Penjernihan Air Tanah dengan Carbon Filter Mengacu pada Permenkes Nomor 2 Tahun 2023 - Rahmi, Viona Aulia; Thoriq Fajri , Muhammad; Aulia Sari Ermal , Dini; Fratiwi , Megawati; Oktaviandi , Ryan; Nabila , Roida (Fakultas Teknik UMRI, 2026)
Although groundwater is the primary source of clean water for most Indonesians, its quality is often compromised by physical and chemical parameters that exceed safe limits, such as high turbidity, a pungent odor, and excessive concentrations of iron (Fe) and manganese (Mn). This study focused on testing the effectiveness of groundwater purification using activated carbon filter media in a Fiber Reinforced Plastic (FRP) tube filtration system. This study evaluates filtration performance in accordance with the Environmental Health Quality Standards (SBMKL) for sanitation and hygiene purposes, as stipulated in Regulation of the Minister of Health (Permenkes) of the Republic of Indonesia No. 2 of 2023. The experimental results show that the activated carbon filter operates efficiently; it is capable of reducing turbidity by up to 85%, significantly eliminating odors, lowering iron (Fe) levels to meet the quality standards of Permenkes No. 2 of 2023, and reducing the concentrations of manganese (Mn), nitrate, nitrite, and Cr⁶⁺ which were already within the standard range from the outset. Thus, the effluent analysis confirms that the treated water meets regulatory standards and is suitable for daily sanitation needs.